(untitled) (Journal of Economic Research & Business Administration, 2015)
The article considers the charity. The transition period is characterized by intense social situation. This can affect the state’s stability as a whole. In connection with this the society needs socially responsible organizations and businesses. Their social work is important not only for staff but also for society as a whole. The highest level of social responsibility of business is charitable activity. In turn, the charity contributes not only responsible generation but also a socially responsible state.